FACTORS INFLUENCING NURSING STAFF TO GENERATE INCIDENT REPORTS IN MAFRAQ HOSPITAL, ABU DHABI, UAE - Ms. Nadia Tatum, RN, Mr. Sravan Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Generation of incident reports or occurrence variance reports helps healthcare organizations to identify the opportunities for improvement and improve their processes& systems before a substantial injury / mortality / loss happens to the people & organization. Undoubtedly, nursing staff are the top most in reporting of incidents in healthcare organizations and hence it would be interesting to find the factors which influence them to report incidents at workplace.This study was intended to know what influences nurses to report or not report incident reports, identify solutions that can be implemented to improve reporting among nurses and thus find more opportunities for improvement for ensuring patient safety.A cross-sectional study was done using a questionnaire to learn the factors influencing nursing staff to report incidents. The study was conducted at Al Mafraq hospital and cross sectional survey data collected in the months of Nov 2018 to Jan 2019. The questionnaire was sent to 1200 nurses from and 355 of them responded (29.5%). The 1stsection of the questionnaire had demographics captured, 2nd section had 11 questions factors promoting incident reporting and 3rdsection had 9 questions capturing factors preventing staff from reporting incidents. All the questions used 5 point Likert scale (Strongly Agree, Agree, Neutral,